Práticas higiênico-sanitárias na ordenha de vacas e percepção de risco de produtores rurais no Estado de São Paulo - Baraldi, Marina Sanches Romano [UNESP] (2013)
A total of 199 farmers of 116 municipalities in the state of São Paulo, whose main economic activity in 2011 was the dairy cattle were interviewed about hygienic and sanitary practices related to milking cows and related measures. The results revealed that the milking activity were performed by the owners themselves (59.0%), followed by staff and family members, that most producers had milking machine (64.9%) and performed the milking in the milking barn or corral covered (65.9%), or milking parlor (34.1%) with cemented floor ( 69.8%). Respondents also stated that had conditions for the hand hygiene in the places where they perform milking (71.8%) and used to wash their hands regularly (78.9%) using disinfectant (61.8%). The conventional practice of washing the teats with water (52.7%), to dry with a paper towel (52.7%) and the use of disinfectant (53.7%) before milking the cows also prevailed in answers of respondents. In this same focus, the majority of respondents stated they make the mug test before milking (51.7%), the daily removal of manure (82.9%) and wash the place of milking (52.7%) and utensils after use (95.9%). Producers also stated that the milk temperature reach ideal standards in safe period (67.8%) and the lighting and ventilation of the room's milk (82.9%) and milking (76.9%) would be appropriate. Similarly, 50.7% of respondents reported holding the milking line with some criteria and 135 (67.8%) stated that cows treated for mastitis or other diseases were milked in the same room or milking place, along with healthy animals. Moreover, the majority of respondents (59.8%) said they did not have the habit of using appropriate and clean clothes, not disinfect the teats after milking (62.8%) and do not make any test for the detection of subclinical mastitis (53.3%). In most production systems (61.8%) other animals would not have access to the milking room or milking place, whereas...